Editorial - Pacheco Romero, José (2014)
With pleasure we inform our readers that the Peruvian Society of Obstetrics and Gynecology (SPOG) and is the Peruvian Section VI District American Congress of Obstetricians and Gynecologists (formerly American College of Obstetricians and Gynecologists - ACOG). In the future we will be seeing a lot of activity this link SPOG - ACOG. For now, and during the Annual Meeting of the ACOG 2014 has delivered corresponding to the 16 new Fellows (Members Historical SPOG) certificates, with a special Peruvian Congress members who attended the ceremony. The SPOG continue to receive applications for Historical Junior Members and Fellows (obstetrics and gynecology residents) for a few months. Likewise, the Accreditation Committee SPOG-ACOG (CASA) is in ongoing meetings to assist the development of programs in the specialty residentado.